Multinodular Goiter Progression Toward Malignancy in a Case of DICER1 Syndrome: Histologic and Molecular Alterations. Issue 5 (10th March 2018) - Gullo, Irene; Batista, Rui; Rodrigues-Pereira, Pedro; Soares, Paula; Barroca, Helena; do Bom-Sucesso, Maria; Sobrinho-Simões, Manuel
Abstract: Objectives: Multinodular goiter (MNG) and well-differentiated thyroid carcinoma (WDTC) are emerging phenotypes of DICER1 syndrome. Methods: Histologic and molecular findings of botryoid-type embryonal rhabdomyosarcoma (bERMS) and thyroid nodules from a 12-year-old DICER1 mutation carrier (p.Arg1060Ilefs*7) were investigated, providing interesting clues for understanding thyroid carcinogenesis. Results: The patient had bERMS at age 7 years. The thyroid was enlarged and multinodular (61 g). Histologically, some nodules were classified as adenomatous and others as tumors with "intermediate" nuclei. One displayed vascular invasion and was classified as WDTC not otherwise specified (NOS). Somatic DICER1 mutations were identified in bERMS, two tumors with "intermediate" nuclei and WDTC. No somatic DICER1 mutations were found in adenomatous nodules. No molecular alterations were detected in BRAF 600, NRAS 61, HRAS 12/61, KRAS 12/61, TERT promoter, RET/PTC1, RET/PTC3, and PAX8 / PPARγ . Conclusions: The findings obtained from this single case support the assumption that DICER1 syndrome–related WDTC NOS may develop on a background of MNG, via a stepwise process, involving DICER1 somatic mutations and additional molecular events, distinct from the classic pathways of papillary/follicular carcinoma.